(untitled) (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2025)
The emergence of Artificial Intelligence (AI) has triggered a global transformation in production systems, labor markets, and governance structures. This paper explores how AI reshapes the political economy, analyzing the distribution of power, wealth, and control in an automated world. While AI enhances productivity and economic efficiency, it also risks deepening inequality and creating monopolistic concentrations of technological power. Through mixed-method research—integrating policy analysis, quantitative labor data, and qualitative interviews—this study identifies major governance challenges related to employment, regulatory capture, and ethical oversight. The findings highlight that without robust institutional frameworks, AI could exacerbate social divides and weaken democratic accountability. The paper concludes with recommendations for inclusive AI governance that balances innovation, equity, and human well-being.